Workshop Online Merajut Menggunakan Video Sebagai Media Tutorial - Dias Ayu Budi Utami (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Under the conditions of PPKM (Enforcement of Restrictions on Community Activities), most of the time is spent on gadgets and playing social media (social media). Many activities are also carried out online, for example: school and work which is known as work from home. So all activities are more focused on gadgets. To maximize time productively, it is necessary to hold activities that hone skills. In addition to filling time, these skills can be used to create works that are marketable so that they can increase income. Organizing an online workshop or what is commonly called WSO with knitting activities to make handmade works such as cell phone gloves and key chains is expected to be able to help the community.